2020
DOI: 10.1002/adom.202000713
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Color Temperatures and Emission Enhancement in 1D Halide Perovskites under High Pressure

Abstract: Designing low‐dimensional halide perovskites (LDHPs) for broadband emissions with enhanced emission and preferred chromaticity coordinator or color temperature remains a pressing challenge. Herein, a comprehensive study is conducted about the relationship between the crystal structure and broadband emission properties of 1D halide perovskite C4N2H14PbBr4, one of promising white‐emission LDHPs. It is found that the zigzag distortion degree tuned by pressure not only suppresses the general photoluminescence quen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 29 publications
(32 reference statements)
2
40
0
Order By: Relevance
“…[ 26,27 ] The corresponding Commission Internationale de l'Éclairage (CIE) coordinates of the emission are (0.04454, 0.3772) at room temperature (Figure 3B), which corresponds to a relative correlated color temperature of 2500 K and warm orange light. [ 15 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 26,27 ] The corresponding Commission Internationale de l'Éclairage (CIE) coordinates of the emission are (0.04454, 0.3772) at room temperature (Figure 3B), which corresponds to a relative correlated color temperature of 2500 K and warm orange light. [ 15 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 10 ] Despite the initial discovery, and a similar paper on perchlorate perovskites in 2011, [ 11 ] advancements have been reported only during the past two years, including an understanding of their optically active non‐centrosymmetric, ferroelectric and mechanical properties [ 12,13 ] and, most recently, their intrinsic charge transport properties. [ 14 ] The rich investigations of metal‐based perovskites have enabled discoveries of how charges recombine for light emission, color tuning, bandgap tuning by manipulating the structure, and charge extraction control for better photoresponse, [ 15–17 ] which place metal‐based halide perovskites in a dominant position for perovskite optoelectronics. However, in contrast to their metal‐based analogs, for metal‐free perovskites, these fundamental properties still remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that an optimal distortion in metal halide perovskites is preferred to determine the PIE. [ 26,28–30 ] In addition, Li et al. reported an irreversible phase transition of acetamidinium nitrate by introducing CH 3 to impart steric hindrance, thus increasing the potential barrier of phase transition to stabilize the high‐pressure phase.…”
Section: Introductionmentioning
confidence: 99%
“…22 Thus, PIE provides distinct advantages for light-emitting applications achievable by the design of structural distortion. [23][24][25][26] Localization of carriers resulting from a low electronic dimension and seriously distorted metal halide octahedra enhance the optical activity and binding energy of STEs. Therefore, the radiative recombination of STEs may also be activated in doped 3D perovskite materials with local carriers by continuously tuning the structural distortion with the assistance of a high-pressure method.…”
Section: Introductionmentioning
confidence: 99%